PERANCANGAN APLIKASI ARSIP DIGITAL DI KONI KOTA SERANG - Babay Suhendri; Syaechurodji Syaechurodji (Program Studi Sistem Informasi, Universitas Banten Jaya, 2022)
The purpose of this research is to analyze and provide input to KONI Serang City which is currently still using conventional methods in managing documentation of various letters. Office documents almost every day in and out of an agency, both incoming letters and other letters related to disposition and reporting to an agency. To store these documents, we need an application that is able to manage each of these documents so that they can be easily retrieved and can be reused. As time goes by, more and more documents are stored or archived, of course, it will take up more space and make it difficult to search when needed again. In addition, archiving documents with printed files will get damaged over time, therefore this really needs more serious attention considering that every document is very important and valuable. Archival documents that have been piled up. One solution to overcome the problems above is to design a digital archive system, where with this digital system every document will be archived properly and safely and make it easier to search when needed again, besides that it will save space and time. The research methods used include data collection methods by interview, observation and literature study, the approach method used is structured, namely the system development method using the waterfall model. After conducting analysis, design and testing, it is concluded that with this system mail management is better, simplifying the process of managing each document so that there is no more delayed reporting or information.